Pengaruh Faktor Fundamental Perusahaan terhadap Return Saham Sektor Keuangan Syariah yang Terdaftar dalam Daftar Efek Syariah Tahun 2015-2017 - Kusnadi Kusnadi; Sufyati HS; Ginta Ginting (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
This study aims to analyze the influence of corporate fundamental factors such as ROA (Return on Assets), ROE (Return On Equity), EPS (Earning per Share), NPM (Net Profit Margin), DER (Dept to Equity Ratio) and CR (Current Ratio) of financial sector stock returns listed in the Daftar Efek Syariah (DES). The sample of this study were determined using the saturated sampling method in which all populations were sampled. The research sample consisted of 5 companies with an observation period of 2015-2017 to obtain 15 observational data. Data analysis used multiple linear regression analysis. The results showed that ROA, ROE, EPS, NPM, DER and CR together had a positive and significant effect on stock returns. While partially ROA, ROE, NPM, and CR have no significant effect on stock returns. Only EPS and DER have a positive and significant effect on stock returns. While the most dominant variable influencing stock returns is DER. The theoretical implication of this research was that investors need to consider EPS and DER by looking at the ups and downs of the ratio. Practically, in determining investor stock returns, do not only pay attention to the company's internal factors, but must pay attention to the company's external factors. Keywords: Fundamental Factors, ROA, ROE, EPS, NPM, DER, CR, Stock Return.